IMPLEMENTATION OF ELECTRONIC LAND CERTIFICATES TO INCREASE LEGAL AWARENESS IN LAND REGISTRATION ACTIVITIES - Lidya Christina Wardhani; Facha Zahrul Wardah; Chiko Izza Anfasa Firdaus3, (INTERNATIONAL JOURNAL OF LAW, GOVERNMENT AND COMMUNICATION (IJLGC), 2024)
Land registration activities produce a land certificate as proof of ownership of the land that is currently still physically published in book form. It is potentially misuse such as falsification of land certificates, double land certificate, overlapping land ownership, and lost or damaged land certification. In order to facilitate service to the public and to provide legal certainty and protection, the change in the form of land certificates from physical models to electronic land certificate is an activity undertaken by the Government. The method of approach used in this writing is normative jurisprudence through written legal study of various aspects that support the interpretation of material according to the formula of the problem. The results of this research are that with the existence of an electronic land certificate the needs of the community are expected to be met effectively and efficiently. By changing the physical form of the certificate to electronic, the aim is to raise public awareness to register their land, and to provide better legal certainty and protection. Therefore, in its use and use must be in accordance with the rules that have been established by the Government, the Government should also increasingly optimize the application of electronic land certificates.